2022
DOI: 10.1186/s12989-022-00449-y
|View full text |Cite
|
Sign up to set email alerts
|

Coal dust exposure triggers heterogeneity of transcriptional profiles in mouse pneumoconiosis and Vitamin D remedies

Abstract: Background Coal dust particles (CDP), an inevitable by-product of coal mining for the environment, mainly causes coal workers’ pneumoconiosis (CWP). Long-term exposure to coal dust leads to a complex alternation of biological processes during regeneration and repair in the healing lung. However, the cellular and complete molecular changes associated with pulmonary homeostasis caused by respiratory coal dust particles remain unclear. Methods This st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 81 publications
0
9
0
1
Order By: Relevance
“…Coal dust particles were collected in a coal mine in Anhui Province, China. The distribution of the particle size and the microelement content were analyzed in our previous study ( Mu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal dust particles were collected in a coal mine in Anhui Province, China. The distribution of the particle size and the microelement content were analyzed in our previous study ( Mu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…A CWP mouse model was established via the nasal inhalation of coal dust particles. The murine model was reported previously ( Mu et al, 2022 ). Briefly, 20 mice were randomly divided into two groups: a control group (NS) and a coal dust exposure group.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, findings from inhalation studies have been used to show the potential effects of different levels and types of coal mining dust exposure on lung disease. M u et al [ 102 ] intranasally challenged C57BL/6 male mice with coal dust for different durations of time (3, 6 and 9 months) and showed that mice challenged with dust showed structural destruction of lung parenchyma with increased inflammation and upregulation of necrotic, autophagic and apoptotic pathways, which led to cell death and eventually lung fibrosis. These results show that coal dust inhalation in mice can be used to recapitulate key pathological features of CWP and thus is an appropriate platform for understanding the mechanisms of disease pathogenesis.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Several studies have previously signaled that transitional elements such as bioavailable iron or nickel are culpable for the incidence of severe health problems [13][14][15][16]. However, the precise chemical nature and compositional information about the materials inhaled in coal mining areas remain scanty [17][18][19]. This knowledge gap is mainly because most published works on coal and potentially hazardous elements (PHEs) geochemistry focus on the toxic emissions and residues produced during combustion in coal power plants [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise chemical nature and compositional information about the materials inhaled in coal mining areas remain scanty [17][18][19]. This knowledge gap is mainly because most published works on coal and potentially hazardous elements (PHEs) geochemistry focus on the toxic emissions and residues produced during combustion in coal power plants [19,20].…”
Section: Introductionmentioning
confidence: 99%